Influence of Social Determinants of Health Service Quality on Patient Satisfaction at Undata Hospital, Palu - Sudirman Sudirman; Muhammad Nur Ali; Nurdin Rahman (Journal of Public Health and Pharmacy)
Introduction: This study aimed to investigate the effect of social determinants of health service quality on patient’s satisfaction at Undata Regional Public Hospital.